Transatlantic affiliations of scientific collaboration in strategic management: a quarter-century of bibliometric evidence - Kosch, Oskar; Szarucki, Marek (Journal of Business Economics and Management, 2020)
The main objective of the paper is to identify and explore patterns and dynamics of transatlantic scientific collaboration in the field of strategic management between the United States (US) and European countries (EUC) during the last quarter century. Scholarly connections between countries, cities and institutions on the basis of co-author affiliations were analysed to determine the knowledge flow from a geographical perspective. This is the first time international scientific collaboration between researchers in the field of strategic management has been studied to such an extent. We employed all sources of relevant data from the Web of Science and Scopus databases and explored 453 results. Utilizing a bibliometric analysis, our study offers a comprehensive and up-todate identification and assessment of the current situation and dynamics of transatlantic scientific collaboration. The obtained results confirm the dominant role of the US in this type of collaboration. Also, the dominant role of several clusters in terms of collaboration, both on country and institution levels can also be observed. The study confirms the weaker position of Eastern and Central Europe countries in this collaboration and provides some recommendations to increase this type of knowledge exchange in the future.